Heat-conducting silicone grease as well as preparation method and application thereof
By using a branched bottle brush-shaped polydimethylsiloxane as the thermal grease matrix, and performing the combination and surface modification of the thermal filler, the thermal grease migration problem is solved and efficient thermal management performance is achieved.
Patent Information
- Application Number
- CN202411598525.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Existing thermal greases are prone to migration, slippage, cracking and powdering under extreme operating conditions, resulting in thermal management failure.
Bottle brush-shaped polydimethylsiloxane (BBP) containing a large number of branched chains is used as the matrix of thermal grease, and the maximum filling amount and thermal conductivity of thermal grease are improved by combining different particle sizes of thermal fillers and surface modification.
Low migration, easy-to-coat thermal conductivity grease is achieved, reducing oil permeability and viscosity, improving thermal conductivity and maximum filling amount, and enhancing thermal management performance.
Smart Images

Figure CN119570265A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer thermal conductive composite materials, in particular to a low-migration, easy-to-coat thermal conductive silicone grease and a preparation method and application thereof. Background Art
[0002] Thermal grease is a common thermal interface material, usually made of a silicone oil matrix mixed with a high content of thermal conductive fillers, and is used to fill the gap between the heat-generating device and the heat sink. Thermal grease has a low thermal conductivity, but its liquid-like dynamic performance gives it good wetting properties and very low boundary layer thickness (BLT), so it exhibits extremely low contact thermal resistance (Rc) and good cross-interface heat transfer capabilities in thermal management.
[0003] At present, low molecular weight, non-cross-linked polydimethylsiloxane (PDMS) is widely used as the silicone oil matrix of thermal grease due to its good molecular chain flexibility and good fluidity. Therefore, the thermal grease can be evenly assembled on the surface of the heat source by coating. This simple construction makes it widely used in various low BLT thermal management occasions. However, the small molecule matrix in the thermal grease is easy to pump out and migrate. This phenomenon will even be further aggravated under long-term extreme working conditions, and eventually the thermal grease will slip, crack and powder, resulting in thermal management failure ( Figure 1 ).
[0004] In order to solve the migration problem of thermal grease, some researchers use high molecular weight PDMS as the matrix of thermal grease. However, the use of high molecular weight PDMS increases the viscosity of thermal grease, seriously affecting its coating performance. In addition, PDMS thermal conductive gel with a cross-linked network has also been developed. The matrix of the thermal conductive gel can be slightly cross-linked at a certain temperature to form a polymer network structure. Although the cross-linked network solves the oil migration problem of thermal grease, the two-component formula of the thermal conductive gel makes its assembly process complicated. In order to simplify the assembly process, a single-component thermal conductive gel using a microencapsulated platinum catalyst or a high-efficiency inhibitor has also been developed, but its limited stability makes it difficult to store for a long time.
[0005] Currently, some non-reactive thermally conductive gels have appeared, but the higher modulus increases the BLT of the thermally conductive gel and the wetting properties are also reduced. Summary of the invention
[0006] In order to solve the above problems existing in the prior art, the present invention provides a low-migration, easy-to-coat thermal conductive silicone grease and a preparation method and application thereof.
[0007] One of the purposes of the present invention is to provide a thermally conductive silicone grease comprising bottle brush-shaped polydimethylsiloxane and a thermally conductive filler.
[0008] Branched polymers have a linear polymer backbone and a large number of branches connected to the backbone. Compared with linear polymers, branched polymers have larger intermolecular chain spaces and less regular spatial structures between the main chains, which inhibits intermolecular chain entanglement and regular arrangement. Therefore, branched polymers generally have lower viscosity while not forming a cross-linked network and having a higher molecular weight. The present invention uses bottle brush-like polydimethylsiloxane (BBP) containing a large number of branches as the matrix of thermal grease, which helps to solve the oil migration problem of traditional thermal grease while ensuring good coating properties of the thermal grease.
[0009] Taking the thermal conductive silicone grease as 100wt%, the content of the thermal conductive filler is 70-96wt%, preferably 80-95wt%, for example, 70wt%, 75wt%, 80wt%, 85wt%, 90wt%, 95wt%, 96wt%, etc.
[0010] In the bottle brush polydimethylsiloxane:
[0011] The main chain length is 200 to 30000 g / mol, preferably 5000 to 15000 g / mol, for example, 200 g / mol, 500 g / mol, 1000 g / mol, 2000 g / mol, 3000 g / mol, 4000 g / mol, 5000 g / mol, 6000 g / mol, 7000 g / mol, 8000 g / mol, 9000 g / mol, 10000 g / mol, 15000 g / mol, 20000 g / mol, 25000 g / mol, 30000 g / mol, etc.;
[0012] The length of the branch chain is 20 to 1200 g / mol, preferably 50 to 1000 g / mol, for example, 20 g / mol, 40 g / mol, 50 g / mol, 100 g / mol, 200 g / mol, 300 g / mol, 400 g / mol, 500 g / mol, 600 g / mol, 700 g / mol, 800 g / mol, 900 g / mol, 1000 g / mol, 1100 g / mol, 1200 g / mol, etc.;
[0013] The branch density is 5 to 70 mol%, preferably 20 to 50 mol%, for example, 5 mol%, 10 mol%, 20 mol%, 30 mol%, 40 mol%, 50 mol%, 60 mol%, 70 mol%, etc.
[0014] The thermally conductive filler is selected from at least one of aluminum, aluminum oxide, zinc oxide, silicon nitride, diamond, boron nitride, carbon nanotubes, carbon fiber, graphite, and graphene.
[0015] Although BBP has a low viscosity, the branched polymer as the matrix of thermal grease will affect the maximum filling amount of thermal conductive filler in the thermal grease, thereby affecting the thermal conductivity of the thermal grease. The present invention further improves the maximum filling amount and thermal conductivity of the thermal grease by compounding thermal conductive fillers of different particle sizes and modifying the surface of the thermal conductive fillers.
[0016] According to a preferred embodiment of the present invention, the thermally conductive filler is a composite thermally conductive filler comprising a nano-sized thermally conductive filler, a submicron-sized thermally conductive filler, and a micron-sized thermally conductive filler.
[0017] More preferably, the nanometer size is 1-99 nm, the submicrometer size is 0.1-0.9 μm, and the micrometer size is 1-100 μm; most preferably, the nanometer size is 60-80 nm, the submicrometer size is 0.3-0.7 μm, and the micrometer size is 1-20 μm.
[0018] In the compound thermally conductive filler, there is no particular limitation on the amount of the nano-sized thermally conductive filler, the submicron-sized thermally conductive filler, and the micron-sized thermally conductive filler, and the amount can be adjusted according to the actual requirements.
[0019] According to a preferred embodiment of the present invention, the thermal conductive filler is surface-modified by a silane coupling agent. The surface modification method can be a common method in the art, or can be adjusted according to actual requirements.
[0020] The silane coupling agent is preferably at least one of dodecylsilane, epoxysilane, aminosilane, mercaptosilane, vinylsilane and methacrylic silane.
[0021] The second object of the present invention is to provide a method for preparing the thermally conductive silicone grease, comprising mixing bottle brush-like polydimethylsiloxane and a thermally conductive filler.
[0022] The bottle brush-like polydimethylsiloxane is prepared by the following steps: polymethylvinylsiloxane having a double bond in the side chain and polydimethylsiloxane with a silicon hydrogen group mono-terminated are reacted in the presence of a Karstedt catalyst.
[0023] According to a preferred embodiment of the present invention, the vinyl content of the polymethylvinylsiloxane having a double bond in the side chain is 5 to 70 mol %, preferably 20 to 50 mol %.
[0024] According to a preferred embodiment of the present invention, the molecular weight of the polymethylvinylsiloxane having a double bond in the side chain is 200 to 30,000 g / mol, preferably 5,000 to 15,000 g / mol.
[0025] According to a preferred embodiment of the present invention, the molecular weight of the silyl mono-terminated polydimethylsiloxane is 20 to 1200 g / mol, preferably 50 to 1000 g / mol.
[0026] In the preparation method, the molar ratio of vinyl group to silyl hydrogen group is 0.5 to 1.5, preferably 0.9 to 1.1.
[0027] In the preparation method, based on the silicon hydrogen mono-terminated polydimethylsiloxane, the platinum content of the Karstedt catalyst is 10 to 500 ppm, preferably 50 to 150 ppm.
[0028] In the preparation method, the reaction temperature is 0 to 100° C., preferably 20 to 50° C.; the reaction time is 1 to 20 hours, preferably 3 to 5 hours.
[0029] In the preparation method, after the reaction is completed, the catalyst is quenched by using a strong polar compound such as imidazole or cyanide; finally, the crude product is washed and dried by using an alcohol or ether solvent.
[0030] The third object of the present invention is to provide the application of the thermal conductive silicone grease or the thermal conductive silicone grease obtained by the preparation method in thermal interface materials.
[0031] The present invention has the following advantages:
[0032] (1) The yield of synthesized BBP was as high as over 95%. The polymer dispersion index (PDI), branch length, density and main chain length of BBP could be determined according to the PVMS and SEH-PDMS raw materials (Table 1, Figure 3 ) to make adjustments;
[0033] (2) By compounding thermally conductive fillers of different particle sizes and modifying the surface of the thermally conductive fillers with silane coupling agents, the maximum filling amount of the thermally conductive fillers in the thermally conductive silicone grease reaches more than 80wt%, and the thermal conductivity of the thermally conductive silicone grease is improved (Table 2);
[0034] (3) Compared with the traditional linear PDMS-based thermal grease, BBP-based thermal grease has lower oil permeability, lower viscosity and lower BLT (Table 3). BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Schematic diagram of the failure mode of thermal grease in the prior art.
[0036] Figure 2 Schematic diagram of the structure of bottle brush polydimethylsiloxane (BBP).
[0037] Figure 3 The hydrogen nuclear magnetic resonance spectra of the raw material mixture and the bottle brush polydimethylsiloxane of Preparation Example 1-4 are shown. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.
[0039] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.
[0040] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation method disclosed in the prior art.
[0041] According to a preferred embodiment of the present invention, the method for preparing the thermal conductive silicone grease may include the following steps:
[0042] (1) Based on the hydrosilylation reaction of Karstedt catalyst, polymethylvinylsiloxane (PVMS) with a large number of double bonds in the side chain and silyl-terminated polydimethylsiloxane (SEH-PDMS) are synthesized by stirring them at a certain temperature. After the reaction is completed, the catalyst is quenched with a strong polar compound such as imidazole or cyanide. Finally, the crude product is washed and dried with an alcohol or ether solvent to obtain BBP.
[0043] Among them, preferably, the vinyl content of PVMS is 5-70 mol%, preferably 20-50 mol%; the molecular weight is 200-30000 g / mol, preferably 5000-15000 g / mol. The molecular weight of SEH-PDMS is 20-1200 g / mol, preferably 50-1000 g / mol. The molar ratio of vinyl to silicon hydrogen is 0.5-1.5, preferably 0.9-1.1. The amount of Karstedt catalyst is 10-500 ppm, preferably 50-150 ppm. The ambient atmosphere is nitrogen, argon, air, etc., preferably nitrogen atmosphere. The reaction temperature is 0-100°C, preferably 20-50°C. The reaction time is 1-20h, preferably 3-5h.
[0044] (2) Thermal conductive fillers such as aluminum, aluminum oxide, zinc oxide, silicon nitride, diamond, boron nitride, carbon nanotubes, carbon fiber, graphite, graphene, and their combinations are introduced into BBP, and conventional equipment such as a non-invasive homogenizer, a double planetary mixer, and a three-roll grinder are used to uniformly mix BBP and the thermal conductive fillers to prepare a low migration, easy-to-coat thermal conductive silicone grease.
[0045] In addition, nano-submicron-micron-sized thermally conductive fillers are compounded to achieve the densest packing of thermally conductive fillers in thermally conductive silicone grease. Furthermore, silane coupling agents are used to modify the surface of the thermally conductive fillers to increase the maximum filling amount of the fillers.
[0046] Specifically, the nanometer size is 1 to 99 nm, the submicrometer size is 0.1 to 0.9 μm, the micrometer size is 1 to 100 μm, the nanometer size is preferably 60 to 80 nm, the submicrometer size is preferably 0.3 to 0.7 μm, and the micrometer size is preferably 1 to 20 μm.
[0047] The silane coupling agent is dodecylsilane, aminosilane, epoxysilane, aminosilane, mercaptosilane, vinylsilane, methacrylate silicon, etc., preferably dodecylsilane. The amount of silane coupling agent is 1-20wt% of the thermal conductive filler, preferably 5-10wt%. The proportion of thermal conductive filler in thermal conductive silicone grease is 70-96wt%, preferably 80-95wt%.
[0048] In the present invention, the test method is as follows:
[0049] Oil permeability test method: Apply 0.5g of thermal grease on filter paper, heat at 100℃ for 30h, and measure the ratio of the oil stain diameter to the initial sample diameter.
[0050] Viscosity: The viscosity at different strain rates at room temperature was tested using a rotational rheometer.
[0051] Thermal conductivity, interfacial thermal resistance, BLT: ASTM D5470-17.
[0052] Preparation Example 1
[0053] 5 g of SEH-PDMS (1000 g·mol -1 ), 4.2 g of PVMS (7559 g·mol -1 ), Karstedt catalyst (platinum content is 100ppm of SEH-PDMS), the molar ratio of vinyl to silicon hydrogen is 1, and magnetic stirring is performed in a constant temperature oil bath under nitrogen protection. The oil bath temperature is set to 30°C and the reaction is carried out for 4 hours. After the reaction is completed, the catalyst is quenched with imidazole. Finally, the crude product is washed and dried with methanol to obtain BBP-1. The yield is 98%.
[0054] Preparation Example 2
[0055] 5 g of SEH-PDMS (1000 g·mol -1 ), 1.2 g of PVMS (7591 g·mol -1), Karstedt catalyst (platinum content is 100ppm of SEH-PDMS), the molar ratio of vinyl to silicon hydrogen is 1, and magnetic stirring is performed in a constant temperature oil bath under nitrogen protection. The oil bath temperature is set to 50°C and the reaction is carried out for 3 hours. After the reaction is completed, the catalyst is quenched with imidazole. Finally, the crude product is washed and dried with methanol to obtain BBP-2. The yield is 98%.
[0056] Preparation Example 3
[0057] 5 g of SEH-PDMS (1000 g·mol -1 ), 0.9 g of PVMS (7429 g·mol -1 ), Karstedt catalyst (platinum content is 100ppm of SEH-PDMS), the molar ratio of vinyl to silicon hydrogen is 1, and magnetic stirring is performed in a constant temperature oil bath under nitrogen protection. The oil bath temperature is set to 40°C and the reaction is carried out for 3 hours. After the reaction is completed, the catalyst is quenched with imidazole. Finally, the crude product is washed and dried with methanol to obtain BBP-3. The yield is 99%.
[0058] Preparation Example 4
[0059] 5 g of SEH-PDMS (1000 g·mol -1 ), 0.89 g of PVMS (11150 g·mol -1 ), Karstedt catalyst (platinum content is 100ppm of SEH-PDMS), the molar ratio of vinyl to silicon hydrogen is 1, and magnetic stirring is performed in a constant temperature oil bath under nitrogen protection. The temperature of the oil bath is set to 20°C and the reaction is carried out for 5 hours. After the reaction is completed, the catalyst is quenched with imidazole. Finally, the crude product is washed and dried with methanol to obtain BBP-4. The yield is 95%.
[0060] Example 1
[0061] BBP thermal grease was prepared by mixing BBP-1 with 10g of nano-alumina (70nm) using a non-invasive homogenizer. When the amount of BBP-1 added was 2.7g, a uniform mixture was formed. The maximum filling amount of pure nano-alumina was 79wt%, and the thermal conductivity was 2.7W / mK.
[0062] Example 2
[0063] BBP thermal grease was prepared by mixing BBP-1 into 10g of submicron alumina (0.5μm) using a non-invasive homogenizer. When the amount of BBP-1 added was 3.3g, a uniform mixture was formed. The maximum filling amount of pure nano-alumina was 75wt%, and the thermal conductivity was 1.8W / mK.
[0064] Example 3
[0065] BBP thermal grease was prepared by mixing BBP-1 into 10 g of micronized aluminum oxide (10 μm) using a non-invasive homogenizer. When the amount of BBP-1 added was 3.7 g, a uniform mixture was formed. The maximum filling amount of pure nano-aluminum oxide was 73 wt%, and the thermal conductivity was 2.3 W / mK.
[0066] Example 4
[0067] 2g of nano-alumina (80nm), 3.3g of submicron alumina (0.3μm) and 4.7g of micron alumina (8μm) were surface modified by epoxysilane, and the amount of epoxysilane was 1wt% of the thermal conductive filler to prepare a modified composite filler. BBP-1 was mixed into the modified composite filler by a non-intrusive homogenizer. When the amount of BBP-1 added was 0.75g, a uniform mixture was formed. At this time, the maximum filling amount of the composite alumina was 93wt%, and the thermal conductivity was 4.0W / mK.
[0068] Example 5
[0069] 2g of carbon nanotubes (50nm), 3.8g of submicron silicon nitride (0.4μm) and 4.2g of micron diamond (13μm) were surface modified by dodecylsilane, and the amount of dodecylsilane was 1wt% of the thermally conductive filler to prepare a modified composite filler. BBP-1 was mixed into the modified composite filler by a non-intrusive homogenizer. When the amount of BBP-1 added was 0.53g, a uniform mixture was formed. At this time, the maximum filling amount of the composite thermally conductive filler was 95wt%, and the thermal conductivity was 9.1W / mK.
[0070] Example 6
[0071] 2g of nano zinc oxide (80nm), 3.8g of submicron zinc oxide (0.3μm) and 4.2g of micron aluminum (8μm) were surface modified by dodecylsilane, and the amount of dodecylsilane was 1wt% of the thermal conductive filler to prepare a modified composite filler. 1.1g of BBP-1 and the modified composite filler were mixed evenly by a non-intrusive homogenizer. The prepared thermal conductive silicone grease had an oil permeability of 4.18%, a viscosity of 1500Pa·s, and a BLT of 48.5μm.
[0072] Example 7
[0073] 2g of nano zinc oxide (80nm), 3.8g of submicron zinc oxide (0.3μm) and 4.2g of micron aluminum (8μm) were surface modified by dodecylsilane, and the amount of dodecylsilane was 1wt% of the thermal conductive filler to prepare a modified composite filler. 1.1g of BBP-2 and the modified composite filler were mixed evenly by a non-intrusive homogenizer. The prepared thermal conductive silicone grease had an oil permeability of 3.98%, a viscosity of 1800Pa·s, and a BLT of 58.5μm.
[0074] Example 8
[0075] 2g of nano zinc oxide (80nm), 3.8g of submicron zinc oxide (0.3μm) and 4.2g of micron aluminum (8μm) were surface modified by dodecylsilane, and the amount of dodecylsilane was 1wt% of the thermal conductive filler to prepare a modified composite filler. 1.1g of BBP-3 and the modified composite filler were mixed evenly by a non-intrusive homogenizer. The prepared thermal conductive silicone grease had an oil permeability of 3.78%, a viscosity of 1600Pa·s, and a BLT of 62.5μm.
[0076] Example 9
[0077] 2g of nano zinc oxide (80nm), 3.8g of submicron zinc oxide (0.3μm) and 4.2g of micron aluminum (8μm) were surface modified by dodecylsilane, and the amount of dodecylsilane was 1wt% of the thermal conductive filler to prepare a modified composite filler. 1.1g of BBP-4 and the modified composite filler were mixed evenly by a non-intrusive homogenizer. The prepared thermal conductive silicone grease had an oil permeability of 3.62%, a viscosity of 1900Pa·s, and a BLT of 64.9μm.
[0078] Comparative Example 1
[0079] 2g of nano zinc oxide (80nm), 3.8g of submicron zinc oxide (0.3μm) and 4.2g of micron aluminum (8μm) were surface modified by dodecylsilane, and the amount of dodecylsilane was 1wt% of the thermal conductive filler to prepare a modified composite filler. 1.1g of linear PDMS (350mPa·s, molecular weight is 13700g / mol) and the modified composite filler were mixed evenly by a non-invasive homogenizer. The prepared thermal conductive silicone grease had an oil permeability of 5.6%, a viscosity of 2000Pa·s, and a BLT of 65.0μm.
[0080] Comparative Example 2
[0081] Thermal grease was prepared by mixing PDMS with 10g of nano-alumina (70nm) using a non-invasive homogenizer. When 3.3g of linear PDMS (350mPa·s, molecular weight is 13700g / mol) was added, a uniform mixture was formed. The maximum filling amount of pure nano-alumina was 75wt%, and the thermal conductivity was 2.3W / mK. The oil permeability of the prepared thermal grease was 10.01%, the viscosity was 9900Pa·s, and the BLT was 71.4μm.
[0082] Table 1 Yield and molecular structure of BBP
[0083]
[0084] Table 2 Viscosity of BBP
[0085]
[0086] Table 3 Maximum filling amount and thermal conductivity of thermal grease
[0087]
[0088] Table 4 Oil permeability, viscosity and BLT of BBP thermal grease
[0089]
Claims
1. A thermally conductive silicone grease comprising bottle brush-shaped polydimethylsiloxane and a thermally conductive filler.
2. The thermally conductive silicone grease according to claim 1, characterized in that: The content of the thermal conductive filler is 70-96 wt %, preferably 80-95 wt %.
3. The thermally conductive silicone grease according to claim 1, characterized in that In the bottle brush polydimethylsiloxane: The main chain length is 200 to 30,000 g / mol, preferably 5,000 to 15,000 g / mol; and / or, The length of the branch chain is 20 to 1200 g / mol, preferably 50 to 1000 g / mol; and / or, The branch density is 5 to 70 mol%, preferably 20 to 50 mol%.
4. The thermally conductive silicone grease according to claim 1, characterized in that: The thermally conductive filler is selected from at least one of aluminum, aluminum oxide, zinc oxide, silicon nitride, diamond, boron nitride, carbon nanotubes, carbon fiber, graphite, and graphene.
5. The thermally conductive silicone grease according to claim 1, characterized in that: The thermally conductive filler is a composite thermally conductive filler including nano-sized, submicron-sized and micron-sized thermally conductive fillers.
6. The thermally conductive silicone grease according to claim 5, characterized in that: The nanometer size is 1 to 99 nm, the submicrometer size is 0.1 to 0.9 μm, and the micrometer size is 1 to 100 μm; the nanometer size is preferably 60 to 80 nm, the submicrometer size is preferably 0.3 to 0.7 μm, and the micrometer size is preferably 1 to 20 μm.
7. The thermally conductive silicone grease according to claim 1, characterized in that: The thermal conductive filler is surface-modified by a silane coupling agent, wherein the silane coupling agent is preferably at least one of dodecylsilane, epoxysilane, aminosilane, mercaptosilane, vinylsilane, and methacrylic silane.
8. A method for preparing the thermally conductive silicone grease according to any one of claims 1 to 7, comprising mixing bottle brush polydimethylsiloxane and a thermally conductive filler.
9. The method for preparing the thermally conductive silicone grease according to claim 8, characterized in that The bottle brush polydimethylsiloxane is prepared by the following steps: In the presence of a Karstedt catalyst, a polymethylvinylsiloxane having a double bond in the side chain and a silyl-terminated polydimethylsiloxane are reacted; preferably, The vinyl content of the polymethylvinylsiloxane having a double bond in the side chain is 5 to 70 mol%, preferably 20 to 50 mol%; and / or, The molecular weight of the polymethylvinylsiloxane having a double bond in the side chain is 200 to 30,000 g / mol, preferably 5,000 to 15,000 g / mol; and / or, The molecular weight of the silyl-terminated polydimethylsiloxane is 20 to 1200 g / mol, preferably 50 to 1000 g / mol; and / or, The molar ratio of vinyl groups to silyl groups is 0.5 to 1.5, preferably 0.9 to 1.1; and / or, The platinum content of the Karstedt catalyst is 10 to 500 ppm, preferably 50 to 150 ppm, based on the silane-terminated polydimethylsiloxane; and / or The reaction temperature is 0 to 100° C., preferably 20 to 50° C.; the reaction time is 1 to 20 h, preferably 3 to 5 h.
10. Use of the thermally conductive silicone grease according to any one of claims 1 to 7 or the thermally conductive silicone grease prepared by the preparation method according to any one of claims 8 to 9 in thermal interface materials.
Citation Information
Patent Citations
Multi-branched chain polysiloxane, preparation method thereof and heat-conducting silica gel
CN114539533A
Heat-conducting organic silicon composite material for chip packaging and preparation method of heat-conducting organic silicon composite material
CN117701234A
Polymer for single-component organosilicone heat-conducting gel
CN118271621A
Polymer brush type powder surface modifier as well as preparation method and application thereof
CN118344594A
Heat conductive silicone composition and semiconductor device
US20020014692A1
Cited By
Liquid metal-based composite heat-conducting silicone grease as well as preparation method and application thereof
CN120310265A
Liquid metal-based composite heat-conducting silicone grease, preparation method and application thereof
CN120310265B